Predicting Metabolic Adaptation Under Dynamic Substrate Conditions Using a Resource-Dependent Kinetic Model: A Case Study Using Saccharomyces cerevisiae - Verhagen, K. J. A.; Eerden, S. A.; Sikkema, B. J.; Wahl, S. A. (Frontiers in Molecular Biosciences, 2022)
Exposed to changes in their environment, microorganisms will adapt their phenotype, including metabolism to ensure survival. To understand the adaptation principles, resource allocation base approaches were successfully applied to predict an optimal proteome allocation under (quasi) steady-state conditions. Nevertheless, for a general, dynamic environment, enzyme kinetics will have to be taken into account which were not included in the linear resource allocation models. To this end, a resource dependent kinetic model was developed and applied to the model organism Saccharomyces cerevisiae by combining published kinetic models and calibrating the model parameters to published proteomics and fluxomics datasets. Using this approach, we were able to predict specific proteomes at different dilution rates under chemostat conditions. Interestingly, the approach suggests that the occurrence of aerobic fermentation (Crabtree effect) in S. cerevisiae is not caused by space limitation in the total proteome, but rather an effect of constraints on the mitochondria. When exposing the approach to repetitive, dynamic substrate conditions, the proteome space was allocated differently. Less space was predicted to be available for non-essential enzymes (reserve space). This could indicated that the perceived ‘overcapacity’ present in experimentally measured proteomes may very likely serve a purpose in increasing the robustness of a cell to dynamic conditions. Especially, an increase of proteome space for the growth reaction as well as of the trehalose cycle was shown to be essential in providing robustness upon stronger substrate perturbations. The model predictions of proteome adaptation to dynamic conditions were additionally evaluated against respective experimental, measured proteomes, which highlighted the model’s ability to accurately predict major proteome adaptation trends. This proof of principle for the approach can be extended to production organisms and applied for both understanding metabolic adaptation, and improving industrial process design.